2016
DOI: 10.1016/j.adro.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiation therapy is associated with a reduced risk of local recurrence among low risk Merkel cell carcinomas of the head and neck

Abstract: PurposeMerkel cell carcinoma (MCC) is a rare and often aggressive skin cancer. Typically, surgery is the primary treatment. Postoperative radiation therapy (PORT) is often recommended to improve local control. It is unclear whether PORT is indicated in patients with favorable Stage IA head and neck (HN) MCC.Methods and materialsWe conducted a retrospective analysis of 46 low-risk HN MCC cases treated between 2006 and 2015. Inclusion criteria were defined as a primary tumor size of ≤ 2 cm, negative pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 37 publications
(53 reference statements)
0
28
0
2
Order By: Relevance
“…Adjuvant RT to the tumor bed for local control after wide excision may be associated with lower recurrences [ 54 ], although the benefits to overall survival remain controversial. An analysis of 185 patients with localized MCC and margin-negative excision found that adjuvant radiation to the surgical bed did not improve the rate of local control [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adjuvant RT to the tumor bed for local control after wide excision may be associated with lower recurrences [ 54 ], although the benefits to overall survival remain controversial. An analysis of 185 patients with localized MCC and margin-negative excision found that adjuvant radiation to the surgical bed did not improve the rate of local control [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…These include small primary tumors (≤1 cm diameter), negative margin status, no LVI, negative SLNB and no chronic immunosuppression (i.e., lymphoma/leukemia) [18,19,36]. In a small retrospective study on patients with low-risk head-and-neck primary tumors, adjuvant RT was associated with increased local control without a survival benefit [37]. Since all recurrences were salvaged by radiotherapy, adjuvant RT should not routinely be recommended for this patient subgroup but discussed per case.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“… 1 MCC patients have a high (approximately >30%) risk for locoregional recurrences and distant metastases after resection. 2 , 3 , 4 , 5 , 6 For patients who have localized disease with clinically negative draining lymph nodes (American Joint Committee on Cancer [AJCC] eighth edition stage I-IIIA), initial treatment typically consists of wide excision of the primary tumor and sentinel lymph node biopsy (SLNB). 7 Surgery is then often followed by adjuvant conventionally fractionated postoperative radiation therapy (cPORT) (50 Gy in 25 fractions).…”
Section: Introductionmentioning
confidence: 99%
“…7 Surgery is then often followed by adjuvant conventionally fractionated postoperative radiation therapy (cPORT) (50 Gy in 25 fractions). 2 , 3 , 4 , 5 , 6 , 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation